THE PREVALENCE OF STRETCH MARKS (STRIAE DISTENSAE) IN PREGNANT WOMEN WHO PARTICIPATES OF LEGIÃO DA BOA VONTADE INSTITUTION IN CASCAVEL CITY, PR, BRAZIL. (Fiep Bulletin - online, 2016)
Introduction:Stretch marks (striaedistensae) are linear skin lesions, atrophic, well defined and secundary to connective tissue changes. They appear when there is a fast skin stretch. They are often associated by abdominal increase arising from pregnancy. Aim: To verify the prevalence of stretch marks during the gestation period  just as well the esthetic dissatisfaction, localization, aspect and genetic influence. Methods: 30 pregnancy women 15-40 years old were interviewed, who participate of the Legião da Boa Vontade institution in Cascavel city, Parana State, south region of Brazil. It was elaborated a survey with 18 questions by the researchers, applied in May 2014, during pregnant activities time. For the statistical analysis, the data were tabulated on Microsoft Office Excel 2013 and subsequently analyzed on SPSS 15.0 software. Results:The results showed that 93.3% of women have stretch marks, however, 53.3% already had stretch marks before the gestation, 43.3% noticed the aggravation, and 40.0% noticed that in gestation period occurred the appearing of stretch marks. Therefore, the prevalence of stretch marks during gestation was 83.3%, the most common locations affected were abdomen and breasts, the occurrence of stretch marks causes worries about body and bad feelings in these women. Conclusion: The study revealed high prevalence of stretch marks during gestation period, what indicates that the gestation is an indicative factor for stretch marks emergence and worsening of stretch marks due to the stretching that occurs with tissue.
Keywords: Stretch marks; pregnancy; prevalence.